Examining the relationship between acculturation levels, help-seeking attitudes, and self-stigma perspectives among international students - Rudra, Praveen Kumar (Journal of International Students, 2025)
This study examined the relationship between acculturation level, help-seeking attitude, and self-stigma among international students enrolled in the graduate counseling program (ICS) within the United States. The Theory of Planned Behavior (TPB) served as the theoretical framework. Using the TPB construct in the context of mental health concerns, this study investigated the relationship between acculturation level, help-seeking attitude, and self-stigma. The data from ASSIS, IASMHS, and SSOSH were analyzed using the Pearson product moment correlation (Pearson r). It was found that the Pearson product-moment correlational analysis between the variables concluded a strong direct correlation between the acculturation level and the help-seeking attitude and acculturation level and self-stigma showed a moderate direct correlation. This suggests that ICS attitude towards mental health services is positive as they experience higher acculturation stress level and that higher acculturation stress levels are associated with greater self-stigma.